Dalitz analysis of D-0 -> K-S(0)pi(+)pi(-) - Muramatsu, H; Richichi, S; Severini, H; Skubic, P; Dytman, SA; Mueller, J; Nam, S; Savinov, V; Chen, S; Hinson, J; Lee, J; Miller, D; et al. (2002)
The resonant substructure of the decay D0→KS0π+π- was analyzed using the Dalitz technique. Ten contributions were observed including a wrong sign D0→K*(892)+π- amplitude with a significance of 5.5 standard deviations.